Studying the regulation of endosomal cAMP production in GPCR signaling - Gidon, Alexandre (Methods Cell Biol, 2015)
We describe methods based on live cell fluorescent microscopy and mass spectrometry to characterize the mechanism of endosomal cAMP production and its regulation using the parathyroid hormone (PTH) type 1 receptor as a prime example. These methods permit to measure rapid changes of cAMP levels in response to PTH, kinetics of endosomal ligand–receptor interaction, pH changes associated with receptor trafficking, and to identify the endosomal receptor interactome.